Aerobic training as an approach to increasing VO2max in amateur football athletes - Marsuna; Hudain, Muh. Adnan; Heriansyah (UIR Press, 2024)
Background Problems: Lack of variety in aerobic exercise can cause boredom and reduce motivation to increase VO2max. Research Objectives: This study aims to assess how much influence aerobic exercise has on increasing VO2max in amateur football athletes. This involves regularly monitoring and measuring changes in VO2max levels over time. Methods: This research used a pre-experimental method; the design used was a one-group pretest and posttest design. The study used total sampling to select a population and sample of 30 amateur athletes. The instrument used was the 15-minute balke test to determine the athlete's VO2max capacity. The method used aerobic training with a 400-metre run. The data analysis technique used descriptive statistical tests, and prerequisite tests were normality, homogeneity, and hypothesis testing using the t-test with the SPSS version 26 program. Findings and Results: The analysis of the data reveals a notable improvement in VO2max following aerobic exercise. The average VO2max value increased from 55.38 during the pretest to 70.70 in the posttest phase. This increase was substantiated by the t-test results, where the calculated t-value was 10.36. Consequently, this indicates a significant enhancement in VO2max post-exercise. Conclusion: Aerobic exercise has a crucial role in increasing VO2max in amateur football athletes. Good cardiorespiratory conditioning can help improve their endurance, performance, and recovery during training and competition.